The Role of Local Governments in Optimizing Regional Original Revenue: A Role Theory Perspective on Fiscal Autonomy - Sa'bani, Shaghi Ratu; Saputro, Guntur Eko; Suwito, Suwito (PPSDP International Journal of Education, 2025)
Regional autonomy grants significant authority to local governments to manage regional potential and improve society’s welfare. One of the indicators of the success of regional autonomy is fiscal independence in managing regional finances. Although decentralization policies have been implemented for a long time, local governments still rely on central funding for routine and regional development expenditures. The abundance of authority granted by the central government to local governments forms the basis for local government’s decisions and actions in planning regional development and welfare through the optimization of regional original revenue (PAD). This study examines the strategic role of local governments in optimizing regional original revenue as a step toward fiscal independence. The study uses qualitative methods and descriptive techniques, applying Biddle and Thomas's role theory, which focuses on behavior, conflict, and ambiguity in roles. The results show that the role theory framework highlights the complexity of local government functions, where role conflicts and ambiguities hinder effective revenue management. Strengthening governance, improving administrative capacity, leveraging digital solutions, and enhancing public awareness are key to optimizing PAD collection. Clear role allocation and coordination among agencies are crucial to reducing dependency on central funding and ensuring sustainable regional development.